The effect of protein deficiency on body weight on muscle in hind limbs of the male rats - Nasser Hussein, Abbas; Abdul Kareem, Hashim Mohammed (Al-Qadisiyah Journal of Pure Science, 2018)
This study included a knowledge of the changes that occur on body weight and muscle of hind limbs to a male rats (Soleus, Gasrocnemuis, Rectus Femoris). Was used in this study, 18 male rats from the age of 2 month, divided into three groups, the first group (control), which was given a diet containing 20% â€‹â€‹crude protein with other components of the diet, the second group (Group 10% protein) that was given a 10% crude protein with other feed ingredients, the third group (Group 5% protein) that has been give diet containing 5% crude protein with components of the bush, the other study lasted six weeks (42) days where conducted from 27 October 2015 to 21 January 2016. The study results showed obtain significant decrease (P <0.05) in the weights of the animals’ bodies. It showed results of the examination histocompatibility of the muscles in the third group (Group 5% protein) atrophy of the muscle fiber with expanded trabeculae between the muscle fiber and necrosis in some muscle fibers that appear pale and the proliferation of cells inflammatory volatile as well as bleeding with accidental planning loss. Which protein deficiency effect on weight of body and also protein deficiency has effect on muscles of hindlimbs of male rats.